Traumatic injuries of the knee - Rodriguez-Merchan, E. Carlos (Springer Milan, 2013)
This book reviews the most important traumatic injuries that occur around the knee joint, providing detailed information on mechanisms of injury, diagnosis, and treatment. A wide range of injuries are covered, including jumper's knee, meniscus tears, knee ligament injuries, knee extensor mechanism injuries, and the floating knee. Dislocations of the knee and patella are carefully considered. Osteochondral fractures and fractures of the distal femur and tibial plateau are discussed in individual chapters that provide clear guidance on treatment. The book closes by reviewing the management of malunion and non-union about the knee. The authors are acknowledged experts in the field and have taken care to ensure that all information is completely up to date. This well-illustrated and instructive book will be of value to orthopedic surgeons, sports medicine specialists, and others who work with patients with traumatic knee injuries.